Electrochemical Formation of p-Type Bi0.5Sb1.5Te3Thick Films onto Nickel - Matthew Burton (Journal of The Electrochemical Society, 2017)
Bismuth-telluride-based alloys are currently the best commercially available thermoelectric materials for applications at room temperatures. Up to 150 micron thick layers of bismuth antimony telluride (Bi0.5Sb1.5Te3) were directly deposited onto nickel by either potenstiostatic or potentiodynamic electrodeposition. Cyclic voltammetry was employed to identify the optimal deposition potential. The films were characterized by scanning electron microscopy, energy dispersive X-rays and X-ray diffraction. The p-type films were found to be well adherent, uniform and stoichiometric with a high power factor of 2.3 × 10−4 W m−1 K−2 at film growth rates of up to 40 μm h−1.